Development of a Native Educational Package for Marital Life Enrichment Based on the Lived Experiences of Successful Couples - Bagheri, Soheila; Honarparvaran , Nazanin; Yarahmadi , Yahya (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to develop a culturally grounded educational package for marital life enrichment based on the lived experiences of successful couples. This study was conducted using a qualitative research design grounded in a phenomenological approach integrated with constructivist grounded theory. The research population included successful couples residing in Shahrekord in 2023, from whom 15 couples were selected through purposive sampling based on theoretical saturation. Data were collected using semi-structured, in-depth interviews, each lasting between 40 and 120 minutes, and transcribed verbatim for analysis. The analytical process followed Charmaz’s grounded theory approach, including open, axial, and selective coding, with constant comparative analysis guiding the development of categories and themes. To ensure rigor and trustworthiness, strategies such as member checking, peer debriefing, and external auditing by six experts were employed. Inter-coder reliability was also assessed using independent coders. Following the qualitative phase, the extracted categories were used to design an educational package, which was subsequently evaluated by 13 experts in family counseling using the Content Validity Index (CVI), with a minimum agreement threshold of 0.80 considered acceptable. The findings resulted in the identification of nine core domains of marital life enrichment, including ethical orientation, emotional security, communication and conflict management, intimacy and affection, individual and relational growth, family role functioning, shared identity, spiritual transcendence, and resilience. These domains were systematically organized into a structured nine-session educational protocol. The expert evaluation demonstrated high content validity across all components, with CVI values ranging from 0.83 to 0.91 and an overall CVI of 0.87, indicating strong agreement regarding the relevance, structure, and adequacy of the developed package. The study provides a comprehensive and culturally grounded framework for marital life enrichment, demonstrating that successful marital relationships are shaped by a dynamic integration of ethical, emotional, communicative, structural, and spiritual factors, and suggesting that the developed educational package is a valid and applicable tool for enhancing marital quality.